Carbon dioxide‐mediated vasomotion of extra‐cranial cerebral arteries in humans: a role for prostaglandins?. (6th April 2016) - Hoiland, Ryan L.; Tymko, Michael M.; Bain, Anthony R.; Wildfong, Kevin W.; Monteleone, Brad; Ainslie, Philip N.
Abstract : Key points: Cerebral blood flow increases during hypercapnia and decreases during hypocapnia; it is unknown if vasomotion of the internal carotid artery is implicated in these responses. Indomethacin, a non‐selective cyclooxygenase inhibitor (used to inhibit prostaglandin synthesis), has a unique ability to blunt cerebrovascular carbon dioxide reactivity, while other cyclooxygenase inhibitors have no effect. We show significant dilatation and constriction of the internal carotid artery during hypercapnia and hypocapnia, respectively. Indomethacin, but not ketorolac or naproxen, reduced the dilatatory response of the internal carotid artery to hypercapnia The differential effect of indomethacin compared to ketorolac and naproxen suggests that indomethacin inhibits vasomotion of the internal carotid artery independent of prostaglandin synthesis inhibition. Abstract: Extra‐cranial cerebral blood vessels are implicated in the regulation of cerebral blood flow during changes in arterial CO2 ; however, the mechanisms governing CO2 ‐mediated vasomotion of these vessels in humans remain unclear. We determined if cyclooxygenase inhibition with indomethacin (INDO) reduces the vasomotor response of the internal carotid artery (ICA) to changes in end‐tidal CO2 ( P ETC O 2 ). Using a randomized single‐blinded placebo‐controlled study, participants ( n  = 10) were tested on two occasions, before and 90 min following oral INDO (1.2 mg kg –1 ) or placebo. Concurrent measurements of beat‐by‐beat velocity, diameter and blood flow of the ICA were made at rest and during steady‐state stages (4 min) of iso‐oxic hypercapnia (+3, +6, +9 mmHg P ETC O 2 ) and hypocapnia (−3, −6, −9 mmHg P ETC O 2 ). To examine if INDO affects ICA vasomotion independent of cyclooxygenase inhibition, two participant subsets (each n  = 5) were tested before and following oral ketorolac (post 45 min, 0.25 mg kg –1 ) or naproxen (post 90 min, 4.2 mg kg –1 ). During pre‐drug testing in the INDO trial, the ICA dilatated during hypercapnia at +6 mmHg (4.72 ± 0.45 vs . 4.95 ± 0.51 mm; P  < 0.001) and +9 mmHg (4.72 ± 0.45 mm vs . 5.12 ± 0.47 mm; P <  0.001), and constricted during hypocapnia at −6 mmHg (4.95 ± 0.33 vs . 4.88 ± 0.27 mm; P <  0.05) and −9 mmHg (4.95 ± 0.33 vs . 4.82 ± 0.27 mm; P <  0.001). Following INDO, vasomotor responsiveness of the ICA to hypercapnia was reduced by 67 ± 28% (0.045 ± 0.015 vs . 0.015 ± 0.012 mm mmHg P ETC O 2 −1 ). There was no effect of the drug in the ketorolac and naproxen trials. We conclude that: (1) INDO markedly reduces the vasomotor response of the ICA to changes in P ETC O 2 ; and (2) INDO may be reducing CO2 ‐mediated vasomotion via a mechanism(s) independent of cyclooxygenase inhibition. Key points: Cerebral blood flow increases during hypercapnia and decreases during hypocapnia; it is unknown if vasomotion of the internal carotid artery is implicated in these responses. Indomethacin, a non‐selective cyclooxygenase inhibitor (used to inhibit prostaglandin synthesis), has a unique ability to blunt cerebrovascular carbon dioxide reactivity, while other cyclooxygenase inhibitors have no effect. We show significant dilatation and constriction of the internal carotid artery during hypercapnia and hypocapnia, respectively. Indomethacin, but not ketorolac or naproxen, reduced the dilatatory response of the internal carotid artery to hypercapnia The differential effect of indomethacin compared to ketorolac and naproxen suggests that indomethacin inhibits vasomotion of the internal carotid artery independent of prostaglandin synthesis inhibition.